COMPUTER ANALYSIS OF INFLUENCE OF TECHNOLOGICAL FACTORS ON FORMATION OF HARD SKIN IN CRYSTALLIZER AT CREATION OF ROUND INGOT IN MNLZ - A. N. Chichko; V. F. Sobolev; M. A. Murikov; A. V. Demin; D. M. Kukuj; V. A. Matochkin (Литьë и металлургия)
The methods and results of analysis on influence of technological factors of the ingot stretching process on dynamics of the hard skin thickness are presented. The analysis of the dynamics of the round ingots hard skin of different diameters at changing of stretching rapidity as applied to M NLZ used at BMZ.